An Emerging Model for Transformative Learning - Norma Nerstrom (Adult Education Research Conference, 2014)
The Nerstrom Transformative Learning Model emerged from a 2013 qualitative study of adult educators’ transformations sparked by graduate programs in adult education. This narrative reviews salient points of the study, demonstrates the use of the model, and presents a visual construction of transformative learning.